“ANALISIS YURIDIS TERHADAP ADDENDUM DALAM AKAD PERJANJIAN PADA PEMBIAYAAN BERMASALAH” (Studi pada Perusahaan Daerah BPR Syari’ah Mustaqim Sukamakmur) - INDAH CAHYANI (PREMISE LAW JURNAL, 2017)
The Regulation of Bank Indonesia Number 10/181PBI/2008 stipulates the settlement and or restructuring of troublesome financing. In the practice of Syaria Banking, the addendum method is preferable to be applied than to make a new agreement for any changes and or additions to the content of a financing agreement. The problems in this research are what factors that constitute the making of the addendum in solving the troublesome financing at BPR (Rural Bank) Syariah Mustaqim Sukamakmur. How are the mechanisms of adding the content of the agreement carried out by BPR Syari’ah Mustaqim Sukamakmur. What are the legal consequences of the addendum related to the settlement of troublesome financing which has been approved related to the settlement of troublesome financing at BPR (Rural Bank) Syaria Mustaqim Sukamakmur Keywords: Addendum, Agreement, and Troublesome Financing